Comparison of the population variance estimators of 2-parameter exponential distribution based on multiple criteria decision making method - S. Lertprapai (2018)
In this paper we study the problems of estimation for the population variance,θ2 in 2-parameter exponential distribution. In 2-parameter exponential distribution, the estimates parameters are where q = ±1,±2 . The purpose of this study is to compare the estimators of θ2 based on the Multiple Criteria Decision Making (MCDM) procedure to obtain the best estimator. The results reveal that the best estimator of θ2 in 2-parameter exponential distribution is θ̂22(-1). © 2013 S. Lertprapai and M. Tiensuwan.